The Impact of an Internet-Based Self-Management Intervention (HeLP-Diabetes) on the Psychological Well-Being of Adults with Type 2 Diabetes: A Mixed-Method Cohort Study - Megan Hofmann; Charlotte Dack; Chris Barker; Elizabeth Murray (Journal of Diabetes Research)
This mixed-method study assessed the impact of an internet-based, self-management intervention (“HeLP-Diabetes”) on the psychological well-being of adults with type 2 diabetes. Nineteen participants were recruited from 3 general practices. Data were collected at baseline and at 6 weeks follow-up. Access to HeLP-Diabetes was associated with a significant decrease in participants’ diabetes-related distress (Z=2.04, p=0.04, and d=0.28). No significant differences were found in emotional distress or self-efficacy. The qualitative data found that participants reported improvements including increased self-efficacy and support, better management of low mood, greater diabetes awareness, and taking the condition more seriously. Participants also reported making improvements to their eating habits, exercise routine, and medical management. Some negative experiences associated with using the intervention were mentioned including feelings of guilt for not using the intervention as suggested or not making any behavioral changes, as well as technical and navigational frustrations with the intervention. Internet-based self-management interventions may have the potential to decrease diabetes-related distress in people with type 2 diabetes. The qualitative data also suggests internet interventions can positively impact both psychological and behavioural outcomes of adults with type 2 diabetes.